IMPLEMENTASI PERATURAN MAHKAMAH AGUNG RI NOMOR 1 TAHUN 2016 TENTANG TATACARA MEDIASI DI PENGADILAN AGAMA SUMATERA SELATAN - Tamudin, M. (Nurani, 2019)
This study aims to answer the problem: How is the implementation of the Supreme Court Regulation No. 1 of 2016 in the Religion Court in South Sumatra and what factors influence the implementation of Supreme Court Regulation No. 1 of 2016 in the Religion Court in the South Sumatra region? the research can be known: First, Implementation of Supreme Court Regulation No. 1 of 2016 in the Religion Court of South Sumatra region has been running in accordance with procedures established in PERMA Number 1 of 2016, but the success of mediation has not been optimal and effective, this can be seen The report on the success of the mediation recapitulation only reached 10.9% -14% in 2016 and 2017. Second, the factors that influence the implementation of the Supreme Court Regulation Number 1 of 2016 in the Religion area of ​​the South Sumatra region are strongly influenced by factors: a. mediator (in this case a judge mediator) who must have the knowledge, skills and attitudes that support the mediation process; b. litigant parties must have good intentions to resolve disputes through a mediation process and want to be present in the mediation process; c. advocate support who will assist his clients in dispensing disputes through mediation; and D. Good facilities and infrastructure strongly support the success of the mediation process.